2016
DOI: 10.1021/acs.jpcc.6b08093
|View full text |Cite
|
Sign up to set email alerts
|

Solving the “Magic Angle” Challenge in Determining Molecular Orientation Heterogeneity at Interfaces

Abstract: It is critical to determine conformations of molecular monolayers in order to understand and control their functions and properties, such as efficiencies of self-assembly-based biosensors and turnover frequency of surface-bound electrocatalysts. However, surface molecules of the monolayers can adopt conformations with many different orientations. Thus, it is necessary to describe the orientations of surface molecular monolayers using both mean tilt angle and orientational distribution, which together we refer … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
22
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 77 publications
2
22
0
Order By: Relevance
“…Therefore, in such cases the Bloch assumption can give a reasonable description of the vibrational dynamics [112,135,136]. Molecules in the monolayer at the surfaces are usually packed and ordered with limited orientational fluctuation and disorder [31,76,137]. Polarization SFG-VS measurement have shown that even the water molecules at the top-layer of the air/water interface is well-ordered [83,138].…”
Section: Sfg-vs As a Two-dimensional Nonlinear Spectroscopymentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, in such cases the Bloch assumption can give a reasonable description of the vibrational dynamics [112,135,136]. Molecules in the monolayer at the surfaces are usually packed and ordered with limited orientational fluctuation and disorder [31,76,137]. Polarization SFG-VS measurement have shown that even the water molecules at the top-layer of the air/water interface is well-ordered [83,138].…”
Section: Sfg-vs As a Two-dimensional Nonlinear Spectroscopymentioning
confidence: 99%
“…Thus, the vibrational spectral lineshape based on Bloch dynamics model will be explicitly discussed along with the development of the HR-BB-SFG-VS in this review. However, spectral diffusion might be significant for interfacial species, particularly water species at aqueous interfaces [140,141], and the explorations of the higher order SFG-VS spectroscopy, such as 2D-SFG-VS, are important and shall bring in new details of the surface spectral lineshape and dynamics of the surface interactions [26,28,107,137,142].…”
Section: Sfg-vs As a Two-dimensional Nonlinear Spectroscopymentioning
confidence: 99%
See 1 more Smart Citation
“…Previous attempts were mainly concentrated on vibrational SFG (VSFG) experiments. 22,26 In particular, recent efforts in a femtosecond broadband IR source have revolutionized VSFG experiments in terms of both ultrafast time scale 30,39,54,[62][63][64][65][66] and high-resolution spectrum. 51,67 On the other hand, the development of electronic sum frequency generation (ESFG) is much left behind.…”
Section: Introductionmentioning
confidence: 99%
“…2D SFG at solid-liquid interfaces has a broad range of applications and has been used to study surface-specific signals of CO adsorbed to Platinum electrodes 135 , surface-bound peptides 121 and DNA strands 249 , amyloid fibers 250 as well as metal-carbonyl electro-catalysts 49,251,252 .…”
Section: D Sum-frequency Generation Spectroscopymentioning
confidence: 99%